Algorithms for the solution of flow networks containing open channels - Fan-Young (1994)
Hydraulic networks involving free surface open channel flows have many applications, such as water and wastewater treatment plants, irrigation and drainage systems. In such systems, networks of open channels are interlinked with hydraulic control structures in a complex fashion, and determination of the resulting flow distribution and head-losses in such systems is far more complicated and time consuming than the analogous problem of pipe networks. This is because the relationship between flow and head-loss for free surface flow systems also depends upon the water levels and controls operating within the network. The objective of the research is to develop a model which enables the flow distribution throughout such networks to be determined. [Continues.]